Analysis of maxillary sinus septa by cone-beam computed tomography - Camila Furtado de SOUZA; Adriano de Oliveira LOURES; Daniella Guedes de Figueiredo LOPES; Karina Lopes DEVITO (Universidade Estadual Paulista, 2019)
Abstract Introduction Pneumatization of the maxillary sinus may make it impossible to insert implants directly in the posterior region of the maxilla, and in these cases, the solution is to submit the patient to maxillary sinus floor augmentation surgery. The most common complication of this surgery is sinus membrane perforation. Anatomical variations of the internal space of the sinus, such as the bone septa, may further hamper detachment of this membrane. Objective To evaluate the prevalence and characteristics of sinus septa in patients from the Zona da Mata Mineira (Minas Gerais, Brazil), to offer relevant information for a safer planning of surgeries involving this region. Material and method A total of 120 patients (240 sinuses) were analyzed using cone-beam computed tomography (CBCT) images, verifying the presence of sinus septa and classifying them for size and anteroposterior location. Result Of the 120 patients analyzed, 45 (37.50%) had sinus septa, 66 septa in total. Of these, 33 (50%) were present in the middle region of the maxillary sinus and the mean septum size was 7.23 mm. There was no significant difference in the septum size between the genders or between the right and left sides. Conclusion The high rates of incidence of sinus septa justify their study, which should be based mainly on accurate exams, such as CBCT, since they represent one of the most relevant anatomical variations for the cases of sinus surgeries.